You are on page 1of 2

Powered by www.myengg.

com

INVERSE TRIGONOMETRIC FUNCTIONS

PREVIOUS EAMCET BITS
⎛ −1 ⎞ ⎛1⎞ ⎛ −1 ⎞
1. cos −1 ⎜ ⎟ − 2sin −1 ⎜ ⎟ + 3cos −1 ⎜ ⎟ − 4 tan −1 ( −1) = [EAMCET 2009]
⎝ 2 ⎠ ⎝2⎠ ⎝ 2⎠
19π 35π 47π 43π
1) 2) 3) 4)
12 12 12 12
Ans: 4
2π π 3π π 43π
Sol. − 2 × + 3× + 4 × =
3 6 4 4 12
⎛3⎞ ⎛4⎞ π
2. If sin −1 ⎜ ⎟ + sin −1 ⎜ ⎟ = then x = [EAMCET 2008]
⎝x⎠ ⎝x⎠ 2
1) 3 2) 5 3) 7 4) 11
Ans: 2
⎛3⎞ ⎛4⎞ π 3 4
Sol. sin −1 ⎜ ⎟ + sin −1 ⎜ ⎟ = ⇒ sin −1 = cos −1
⎝x⎠ ⎝x⎠ 2 x x
3 16 9 16
⇒ sin −1 = sin −1 1 − 2 ⇒ 2 = 1 − 2 ⇒ x 2 = 25
x x x x
⎛ ⎛ 1 ⎞⎞
3. The value of x where x > 0 and tan ⎜ sec −1 ⎜ ⎟ ⎟ = sin ( tan −1 2 ) is [EAMCET 2007]
⎝ ⎝ x ⎠⎠
5 2
1) 5 2) 3) 1 4)
3 3
Ans: 2
⎛ 1⎞
Sol. tan ⎜ sec −1 ⎟ = sin ( tan −1 2 )
⎝ x⎠
⎛ 1 − x2 ⎞ ⎛ 2 ⎞
tan ⎜ tan −1 ⎟ = sin ⎜ sin −1 ⎟
⎜ x ⎟⎠ ⎝ 5⎠

1 − x2 2 5
⇒ = ⇒x=
x 5 3
4 1
4. sin −1 + 2 tan −1 = [EAMCET 2005]
5 3
π π π
1) 2) 3) 4) 0
3 4 2
Ans: 3
4 1 4 3
Sol. sin −1 + 2 tan −1 = sin −1 + tan −1
5 3 5 4
4 4 π
= sin −1 + cos −1 =
5 5 2
5. sin x + sin (1 − x ) = cos x ⇒ x ∈
−1 −1 −1
[EAMCET 2004]

1

Powered by www.myengg.com
Powered by www.myengg.com

Inverse Trigonometric Functions
⎧ 1⎫
1) {1, 0} 2) {−1,1} 3) ⎨0, ⎬ 4) {2, 0}
⎩ 2⎭
Ans: 3
π
Sol. sin −1 (1 − x ) = − 2sin −1 ( x )
2
1
1 − x = 1 − 2x 2 ⇒ x = 0,
2
⎡ ⎛1⎞ ⎛ 1 ⎞⎤
6. cos ⎢cos −1 ⎜ ⎟ + sin −1 ⎜ − ⎟ ⎥ = …….. [EAMCET 2003]
⎣ ⎝7⎠ ⎝ 7 ⎠⎦
1 1 4
1) − 2) 0 3) 4)
3 3 9
Ans: 2
⎡ ⎛ 1⎞ ⎛ 1 ⎞⎤
Sol. cos ⎢cos −1 ⎜ − ⎟ + sin −1 ⎜ − ⎟ ⎥
⎣ ⎝ 7⎠ ⎝ 7 ⎠⎦
π ⎡ π⎤
= cos = 0 ⎢∵ sin −1 x + cos −1 x = ⎥
2 ⎣ 2⎦
π
7. If sin −1 x − cos −1 x = , then x = [EAMCET 2002]
6
1 3 −1 − 3
1) 2) 3) 4)
2 2 2 2
Ans: 2
Sol. By verification x = 3 / 2
8. sec 2 ( tan −1 2 ) + cos ec 2 ( cot −1 3) = [EAMCET 2001]
1) 5 2) 10 3) 15 4) 20
Ans: 3
Sol. Let tan −1 ( 2 ) = α and cot −1 ( 3) = β
tan α = 2; cot β = 3
⇒ sec α = 5;cos ecβ = 10
∴ sec 2 α + cos ec 2β = 5 + 10 = 15
9. If tan −1 3 + tan −1 x = tan − 8 , then x = [EAMCET 2000]
1) 5 2) 1/5 3) 5/14 4) 14/5
Ans: 2
Sol. tan −1 3 + tan −1 x = tan −1 8
3+ x 1
=8⇒ x =
1 − 3x 5

\\[[

2

Powered by www.myengg.com